2019
DOI: 10.3390/ijms20235991
|View full text |Cite
|
Sign up to set email alerts
|

UV Treatment Improves the Biocompatibility and Antibacterial Properties of Crystallized Nanostructured Titanium Surface

Abstract: This study describes the production of a new material composed of pure titanium (Ti) metal with a crystallized nanostructure and investigated whether heat treatment and ultraviolet (UV) irradiation improved its biocompatibility and antibacterial properties. We compared the performance of UV-irradiated and non-irradiated Ti nanosheets (TNS) formed by dark alkaline treatment and heating at 600 °C with that of untreated pure Ti nanostructure (positive control). In vitro and in vivo experiments to assess biocompat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 48 publications
0
14
1
Order By: Relevance
“…Additionally, treatment with silver ion application combined with UV-A light exposure had a significantly higher antimicrobial effect than the treatment with any of them alone [ 27 ]. Furthermore, UV combined with heat showed inhibition of bacterial attachment and biofilm formation with antibacterial rates of 60% and 96% after 1 and 6 h, respectively, on crystallized nanostructured titanium [ 28 ]. Likewise, UV-irradiated alkali-treated titanium with nanonetwork structures (TNS) also showed a similar reduction up to 6 h [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, treatment with silver ion application combined with UV-A light exposure had a significantly higher antimicrobial effect than the treatment with any of them alone [ 27 ]. Furthermore, UV combined with heat showed inhibition of bacterial attachment and biofilm formation with antibacterial rates of 60% and 96% after 1 and 6 h, respectively, on crystallized nanostructured titanium [ 28 ]. Likewise, UV-irradiated alkali-treated titanium with nanonetwork structures (TNS) also showed a similar reduction up to 6 h [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, it was observed that both treatment processes resulted in enhanced ALP activity and calcium precipitation compared to the untreated Ti surface, where the plasma-treated samples showed the best performance. Our previous reports [ 53 , 54 , 55 ] showed that both methods result in Ti surfaces with high neonatal bone formation potential in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Further work is needed to determine how best to deliver short wavelengths of light in subgingival sites. The safety issues with ultraviolet (UV) light used for activation need to be addressed [ 102 , 103 ].…”
Section: Structural Enhancements and Experimental Designsmentioning
confidence: 99%